Ethnomathematics and Cultural Values in Madurese Agricultural Activities: An Ethnographic Study for Contextual Mathematics Learning - Firdiansyah, Adin Lazuardy; Dewi, Lusiyana; hasanah, Nur (IndoMath: Indonesia Mathematics Education, 2026)
This study aims to explore and describe the manifestation of ethnomathematics concepts and cultural values contained in the rice farming activities of the Madurese community in Bangkalan and Pamekasan Regencies. This study uses a qualitative approach with an ethnographic design. Data were collected through observation and in-depth interviews with farmers and farm laborers. Data analysis was conducted interactively using the Miles and Huberman model, which includes the stages of data condensation, data presentation, and conclusion drawing, with triangulation techniques as a guarantee of data validity. The research findings indicate the presence of significant mathematical concepts, including counting and calculating activities. Furthermore, the application of the concept of comparison and the system of linear equations and inequalities was found. Culturally, this agricultural activity is based on the tradition of mutual cooperation and a strong philosophy of selfless work, which is reflected in the terms dherrebbhan and urunan. These values are rooted in the principles of equal-average-equal-feeling and equal-high-equal-low, which strengthen social cohesion. This study concludes that integrating ethnomathematics into mathematics instruction in schools can serve as a contextual and cooperative learning tool. This strategy not only helps students understand abstract concepts through agrarian realities but also internalizes the dimensions of the Pancasila Student Profile based on Madurese local wisdom.